The role of robotic segmentectomy for non-small cell lung cancer - Gokce, Anil; Akkas, Yucel; Kocer, Bulent (Archives of Surgery and Clinical Research, 2020)
Segmentectomy may be applied to all segments; superior segmentectomies (lower lobe superior segments for both lungs), lingulectomies (two segments forming lingulas of upper left lobe) and basal segmentectomies (segments other than superior segment for both lungs). In lung segment resections; segmentectomy has an equivalent morbidity, recurrence and survival rate compared to lobectomy, in patients with stage I lung cancer, tumors smaller than 2 cm and within the segmental anatomical limits. Segmentectomy also contributes more to preserving lung function and exercise capacity than lobectomy. In tumor resection; especially in patients with advanced age, insufficient performance or insufficient cardiopulmonary reserve, 2 cm in diameter and acceptable segmental margins may be provided. Limited long-term results show oncological results of robotic approach similar to open and VATS approaches. Robotic approach facilitates surgery with more intuitive movements, greater flexibility and high definition, three-dimensional vision. However, high cost and lack of touch sense are main disadvantages of robotic surgery. New studies are needed to assess quality of life, morbidity, oncological results and cost effectiveness. However, considering development of technology in our age and fact that many surgical robot brands will be released in the near future, it is predicted that disadvantages of robotic surgery will be minimized in the near future. This article reviews experience of segmentectomy in non-small cell lung cancer and discusses benefits and limitations of robotic segmentectomy.